Cytotoxic activity of Ganoderma weberianum-sichuanese isolated from the Lower Volta River Basin of Ghana against human prostate carcinoma (PC-3), leukemic T cell (Jurkat), and plasmacytoid dendritic cell (pDC)-derived acute leukemia (PMDC05) cell lines - Gideon Adotey; Raphael N. Alolga; Abraham Quarcoo; Mohammed Ahmed Gedel; Paul Yerenkyi; Phyllis Otu; Abraham K. Anang; Laud K.N. Okine; Winfred S.K. Gbewonyo; John C. Holliday; Vincent C. Lombardi (PLoS ONE, 2025)
Ganoderma is a genus of medically important fungus that contains at least 80 species, many of which have not been properly evaluated for their anticancer potential. This study was conducted to assess the cytotoxic activity of the mycelial biomass of Ganoderma weberianum-sichuanese isolated from the Lower Volta River Basin of Ghana. The nuclear ribosomal internal transcribed spacer (ITS) region was analyzed to determine the phylogenetic position of this native ganoderma isolate. We then tested its cytotoxic activity against the human carcinoma cell line PC-3 (human prostate), Jurkat (human T lymphoblastoid cell line), derived from an acute T cell leukemia, and PMDC05, a plasmacytoid dendritic cell (pDC) derived from acute leukemia using the 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay. The ITS phylogenetic analysis demonstrated that this native Ghanaian ganoderma isolate belongs to the Ganoderma weberianum-sichuanese species complex. Fractions of the mycelial biomass were found to inhibit significantly (≤ 0.05%) the proliferation and survival of the three cancer cell lines, PC-3, PMDC05, and Jurkat with increasing concentrations and with IC50 values of 27.73 ± 5.25, 21.31 ± 2.40 and 17.09 ± 0.86 μg/mL, respectively compared to Chang liver cells (CVCL_0238) with IC50 value of 75.41 ± 1.95 μg/mL. To the best of our knowledge, these findings demonstrated for the first time, that specific constituents of Ganoderma weberianum-sichuanese are selectively cytotoxic to the three human cancer cell lines, suggesting their potential efficacy in the treatment of malignancies. Future studies to isolate and characterize the biologically active molecules are warranted.